Use of laser capture microdissection for the assessment of equine lamellar basal epithelial cell signalling in the early stages of laminitis - Leise, B. S. (Equine Vet J, 2014)
REASON FOR PERFORMING STUDY: Dysadhesion of the laminar basal epithelial cells (LBEC) from the underlying dermis is the central event leading to structural failure in equine laminitis. Although many studies of sepsis-related laminitis have reported multiple events occurring throughout the lamellar tissue, there is minimal information regarding signalling events occurring specifically in the LBEC. OBJECTIVES: To determine the signalling events in the LBECs during the early stages of carbohydrate induced laminitis. STUDY DESIGN: Experimental study. METHODS: Eight horses were given an overload of carbohydrate (corn starch mixture, CHO) via nasogastric tube. Prior to administration of CHO, lamellar biopsies were taken from the left fore foot (CON). Biopsies were taken from the left hind foot at the onset of fever (DEV) and from the right fore foot at the onset of lameness (OG1). Laminar basal epithelial cells (LBECs) were isolated from cryosections using a LCM microscope. Next generation sequencing (RNA-Seq) was used to identify transcripts expressed in the LBECs for each time point and bioinformatic analysis was performed with thresholds for between group comparisons set at a greater than 2-fold change and p-value ≤0.05. RESULTS: Forty genes (22 increased/18 decreased) were significantly different from DEV time vs. CON and 107 genes (57 increased/50 decreased) were significantly different from OG1 time vs. CON. Significant increases in inflammatory genes were present in addition to significantly altered expression of genes related to extracellular matrix composition, stability and turnover. CONCLUSIONS: Inflammatory response and extracellular matrix regulation signalling was strongly represented at the DEV and OG1 times. These results indicate that the LBEC is not only a casualty but also an active participant in lamellar events leading to structural failure of the digital lamellae in equine laminitis.